Determination of Sex from Epicondylar Breadth of Femur - Rakesh K. Vora; Shailesh M. Patel (Academia Anatomica International, 2019)
Introduction: Sex determination from skeletal remains allows one to narrow the search in individual identification. As the femur shows 75% Variation between individuals, it has been useful for sex determination. There are many possible femoral measurements, but the Epicondylar breadth is routinely considered to be useful for sexing individuals. To date, nothing has been published on other measurements of distal femur, which may be useful if the bone is fragmented, and only lower part of bone is available. This study is an attempt to evaluate sex determination from distal femora of Indian origin. Subjects and Methods: For this study total 208 normal dry human femur bones of known sex were studied, which were collected from various medical colleges of Gujarat. For measurement of Epicondylar breadth of femur, Digital sliding vernier caliper was used. Results: The discriminant function equation for sex determination from Epicondylar Breadth (EB) of femur is:-Y = 0.143 * EB + (-8.334) If Y is < 0 then the sex of the bone is Female and if Y is > 0 then the sex of the bone is Male. Conclusion: With the use of discriminant function score, 87% of femur samples are correctly predicted about sex. The results of this study is particularly useful in a case for sex determination in which the skeletal remains of an individual are incomplete or damaged and thus more accurate bones such as the pelvis or cranium are absent.